1990
DOI: 10.1163/002925990x00176
|View full text |Cite
|
Sign up to set email alerts
|

Ratios and Indexes in Nematode Taxonomy

Abstract: It is proposed to call "Index" the ratios traditionally included in nematode descriptions (ratios a, b, c, V, etc.) when they are used as a numerical expression of an ordered qualitative character (such as the shape or the position of an organ), and to reserve the name of "Ratios" to the entities recently reviewed by Roggen, Revets and Van den Berghe (Nemutofo&z, 1987). It is shown that it is always possible to use an index instead of an ordered qualitative character for describing a shape or a position, as lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Concerning to other plant-parasitic nematodes, Fortuner (1984) noted that the indices a, c, and c' are often useful to accurately identify species of Helicot ylenchus (Steiner, 1945). Fortuner (1990) also revealed that the features related to body size (length and indices of a and b) showed a high correlation to each oth-er for Hirschmanniella belli. Subbotin et al (1999) also stated that morphometric character analysis is suitable for separating populations within the H. avenae group.…”
Section: Discussionmentioning
confidence: 73%
“…Concerning to other plant-parasitic nematodes, Fortuner (1984) noted that the indices a, c, and c' are often useful to accurately identify species of Helicot ylenchus (Steiner, 1945). Fortuner (1990) also revealed that the features related to body size (length and indices of a and b) showed a high correlation to each oth-er for Hirschmanniella belli. Subbotin et al (1999) also stated that morphometric character analysis is suitable for separating populations within the H. avenae group.…”
Section: Discussionmentioning
confidence: 73%
“…Expressing tail length as a ratio of body diameter at the anus is uncertain because the level at the anterior lip is often different from that at the posterior lip, both of which are exible and may protrude in mounted specimens. De Man's ratios are frequently used for summarising measurements despite the fact that theoretical and practical observations show that these ratios are not, as was originally intended, independent of body length (Fortuner, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Note that indices and quantitative data can be combined in a discriminant function analysis when they are not highly correlated (Fortuner, 1990).…”
Section: Discussionmentioning
confidence: 99%